2021
DOI: 10.1164/rccm.202004-1201oc
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin to Reduce Long-Term Infection-associated Adverse Events in Sepsis. A Randomized Trial

Abstract: Supported by grants by the Hellenic Institute for the Study of Sepsis and by bioMérieux. Procalcitonin assays, material for detection of fecal colonization and laboratory training were provided by bioMérieux. Contribution of authors EJGB conceptualized the study design, participated in data analysis and drafting the manuscript, had full access to all of the study data and takes responsibility for their integrity and the accuracy of the analysis. EK participated in data analysis, drafted the manuscript, had ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 33 publications
3
75
0
4
Order By: Relevance
“…This is a substudy of patients with sepsis due to LRTI enrolled in the PROGRESS trial [ 4 ]. PROGRESS was a prospective, multicenter, randomized trial designed to evaluate a procalcitonin (PCT)-guided antibiotic stopping rule compared to standard-of-care treatment, for the incidence of infection-associated adverse events in patients with sepsis (ClinicalTrials.gov NCT03333304, 06/11/2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a substudy of patients with sepsis due to LRTI enrolled in the PROGRESS trial [ 4 ]. PROGRESS was a prospective, multicenter, randomized trial designed to evaluate a procalcitonin (PCT)-guided antibiotic stopping rule compared to standard-of-care treatment, for the incidence of infection-associated adverse events in patients with sepsis (ClinicalTrials.gov NCT03333304, 06/11/2017).…”
Section: Methodsmentioning
confidence: 99%
“…PROGRESS (PROcalcitonin-Guided antimicrobial therapy to REduce long-term Sequelae of infectionS) is a prospective randomized clinical trial aiming to validate the impact of early stop of antibiotics guided by procalcitonin (PCT) in the prevention of infections by multidrug-resistant microorganisms (MDRO) and Clostridiodes difficile [ 4 ]. Enrolled patients had sepsis due to either lower respiratory tract infections (LRTI) or acute pyelonephritis (AP) or primary bloodstream infection (BSI).…”
Section: Introductionmentioning
confidence: 99%
“…After adjustment, no statistically significant effect of the PCTbased protocol was observed on hospital length of stay (AD ¼ -0.14 days, 95%CI: À0.83; 0.55, p ¼ .690), ICU length of stay (AD ¼ 0.03 days, 95%CI: À0. 13…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…acute bronchitis, exacerbations of chronic obstructive pulmonary disease [COPD], and pneumonia) and sepsis, without adverse effects on mortality, length of stay in the intensive care unit (ICU), or length of hospital stay [9][10][11][12] . A recent randomized trial also found that PCT guidance may have benefits on long-term patient outcomes, including lower rates of infection-associated adverse events at 6 months among patients with sepsis 13 . A 2018 systematic review and meta-analysis of 11 RCTs evaluating the impact of PCT guidance in patients with LRTIs found statistically significant reductions in AB duration (weighted mean difference: À2.15 days, 95% confidence interval [CI]: À3.30; À0.99) and in the odds of initiating AB (odds ratio: 0.26, 95%CI: 0.13; 0.52) 10 .…”
Section: Introductionmentioning
confidence: 98%
“…White blood cell count, C-reactive protein and procalcitonin most often used to diagnose bacterial infections[5, 7] while there are no established markers for viral infections. Several European trials demonstrated that procalcitonin-guided management reduces antibiotic use[8, 9]; however, the incremental value of procalcitonin when used along best practice promotion of current guidelines has been questioned and a large US multicenter interventional trial failed to show a reduction in antibiotic use[10].…”
Section: Introductionmentioning
confidence: 99%